Assessment of Health-Related Quality of Life: The Cinderella of Peritoneal Dialysis?. (26th July 2011) - Moreiras-Plaza, Mercedes; Blanco-García, Raquel; Cossio-Aranibar, Cinthya Raquel; Rodriguez-Goyanes, Gloria
Abstract : The studies of quality of life (QoL) are becoming increasingly interesting in clinical setting because their findings have implications for making decisions on resource allocation and health policies. The assessment of health-related QoL is especially directed to patients with chronic illnesses that cause progressive deterioration and limitations, and consume the bulk of financial resources for health. Among these chronic kidney disease and, more specifically the renal replacement therapy, is an important condition. Due to the diagnostic and therapeutic advances, we see a gradual increase both in the number of the dialysis population and its age, which leads to a growing interest in the study of these patients' QoL, as evidenced by more than one thousand articles published on this subject.